ASSESSMENT OF INDONESIA'S LEGAL FRAMEWORK FOR HUMAN RIGHTS IN CORPORATE SETTINGS - Chang, Soonpeel (Badan Pembinaan Hukum Nasional Kementerian Hukum Republik Indonesia, 2024)
Indonesia has long upheld the protection of fundamental human rights and labor rights through its Constitution, laws, and regulations. In recent years, this commitment has evolved to incorporate global discourses on human rights in corporate and business contexts—such as the United Nations Guiding Principles on Business and Human Rights (UNGP)—into its legal framework. Key milestones in this progression include the enactment of Presidential Regulation No. 60 of 2023 on the National Strategy for Business and Human Rights, the formation of bodies such as the National and Regional Task Forces on Business and Human Rights (Gugus Tugas Nasional and Gugus Tugas Daerah Bisnis dan Hak Asasi Manusia), and the introduction of mechanisms like the Business and Human Rights Risk Assessment (Penilaian Risiko Bisnis dan Hak Asasi Manusia). These efforts aim to align Indonesia’s approach with international standards on human rights due diligence. It is important to note that during the rapid industrialization of many advanced economies, corporations often operated with minimal regulatory oversight. In contrast, modern Indonesian companies face numerous legal frameworks while striving for similar economic growth. This contrast highlights the unique challenges Indonesian companies face in pursuing rapid economic growth while navigating an increasingly complex regulatory environment. Indonesia already has a robust foundation of regulations and policies aimed at safeguarding labor rights and improving working conditions. What the country needs is not another layer of regulations that risk confusing and burdening business players, but rather an effective system to enforce its existing legal framework to its fullest potential. Imposing extensive compliance requirements—such as responding to over 140 detailed inquiries and providing exhaustive evidence of human rights safeguards—could overwhelm Indonesian businesses and undermine their global competitiveness. Instead of directly replicating regulatory models from advanced economies, Indonesia should tailor its approach to align with its unique socio-economic landscape. This means prioritizing the optimization of current legal instruments, strengthening the rule of law, and enhancing legal certainty. These measures are more likely to foster sustainable development than introducing overly complex or burdensome new regulations that may not align with the nation’s current stage of growth.